Optimización en el área de tallado de madera para la fabricación de muebles del hogar en la microempresa El Mundo del Mueble. - Jaya Gavilanes, Antoni Fabricio (2021)
This project details the optimization of the wood engraving process in the carving area, through the design and construction of a prototype of a three-axis computerized numerical control machine for wood machining. Focus to the small business in the furnitured world in order to engrave any type of image with a wide range of designs, greater precision, surface finish and less waste compared to the manual carving procedure. The project begins with the characterization of the raw material used, describing the characteristics and properties of MDF wood; In addition, a bibliographic review was carried out on the different carving machines that are currently used in wood engraving workshops. Through descriptive and exploratory research, four solution options were determined for the design of the machine prototype, for the selection of the best alternative the ordinal method of weighted criteria was used. Based on the criteria of precision, price, weight and exchange of mechanical elements, it was established that the prototype of a CNC machine with three spindle axes is the optimal solution for the design, for the 3D modeling of the parts of the structure and the preparation of assembly and detail plans, the solidworks program was used; From the design, the selection of standardized materials and elements was made, finally, the assembly of the different ones of the machine was carried out, for the engraving of an image the Inkscape program was used that allows vectorizing the graph and through the Universal Gcode Sender software to obtain the programming in code "G" that will be read by means of the GRBL arduino program that allows a machine to move on its three coordinated axes generating the machining of the image; To validate the correct functioning of the prototype, some tests were carried out with the carving of different images, as a result of this experimental practice an efficient design was obtained in a way that reduces the cost and the weight which allows to have a quality finish and carving, it has a work area of 12 cm x 16 cm, minimum investment costs for the manufacture of the machine. From the experimental results carried out to the manual vs automated engraving processes, it was determined that the carving process through the machining of the CNC machine reduces waste by 2.87%, it was also established that the CNC machine has a greater precision of the dimensions and required shape, with a tolerance value of ± 0.1 mm.